PEMIKIRAN KALAM MUH}AMMAD ‘ABDUH DALAM TAFSI>R AL-MANA - Bachrudin, Moh (Dialogia: Jurnal Studi Islam dan Sosial, 2015)
Abstract: The opening of ijtihad and taqlid eradication based on the power of reason is the work done by Muh}ammad ‘Abduh. Believing in the power brought Muh}ammad ‘Abduh to understand that human beings have free willing and action (free willing and free action). This called as Qadariyah. Therefore, Muh}ammad ‘Abduh argued that human can do everything. According to him, God's power is not absolute but limited by His sunnah. In explaining about God's deeds, ‘Abduh said that basically everything is good or bad is all happening because of the will of God in accordance with the Sunnah (law of nature) and the order of causality. Humans are given the ability to do many things. But that ability is limited by the laws of nature. This concept relates to the concept of justice, namely the lack dhalim of Allah (nafy al-z}ulm) is absolute, including the believers and unbelievers. The concept is that those who labor, then his deeds will affect the psyche. A charity which is able to affect the soul will get a reply (Jaza> ') good or bad. Keywords: Akal, Kebebasan Manusia, Keadilan Tuhan dan Perbuatan Tuhan